Pengembangan Alat Bantu Belajar Mengetik Cepat Berbasis Open Source - Dwi Sakethi; Machudor Yusman; Ajeng Savitri Puspaningrum (Universitas Lampung, 2013)
The increasing demand in the use of computers in all aspects of life needs people interact with computers more agile. One of them is to type faster. Various methods and applications have been created to help people to type fast but the application commonly used was a paid or trial applications. Because of that, an alternative application is developed to handle the problem. This applications developed using Waterfall method and the Pascal programming language which is considered easier to do for further development, since this applications will be Open Source .Keywords: Open Source, Pascal, Quick Typing.